Application of macro and trace element analyses to identification of upward flow of water from Miocene aquifer into the Warsaw–Berlin ice-marginal valley aquifer (Śrem, Poland) - Śniady, Igor; Dragon, Krzysztof; Siepak, Marcin (Acta Geographica Lodziensia, 2025)
The upward flow of Miocene aquifer waters into the Quaternary aquifer in the Wielkopolska region can negatively affect the quality of the recharged waters. One example of such an area is the Śrem region, where previous studies indicated the occurrence of groundwater upward flow. Accordingly, research was conducted to confirm the current occurrence of upward flow, determine its impact on the water quality of the Warsaw–Berlin ice-marginal valley aquifer, and assess the relationship between selected trace elements (TEs) and the migration of Miocene aquifer waters. For this purpose, cations (Na+, NH4+, K+, Ca2+, Mg2+) and anions (Cl˗, NO3˗, NO2˗, SO42˗, PO43˗) were determined using ion chromatography (IC), and TEs (Al, As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Zn) were measured using inductively coupled plasma triple quadrupole mass spectrometry (ICP-QQQ-MS). The results confirmed the continuous occurrence of upward flow in the Śrem area. This was determined based on the increasing concentrations of Cl⁻, Na⁺, and K⁺, whose rising levels in the waters of the Warsaw–Berlin ice-marginal valley aquifer are associated with the upward flow of Miocene aquifer water. Additionally, it has been shown that the upward flow of Miocene aquifer waters does not significantly affect overall water quality in the Warsaw–Berlin ice-marginal valley. It was also found that the increase in As, Cr, Cu and Zn concentrations with depth in Quaternary groundwater is likely associ-ated with the migration of these TEs from Miocene aquifer waters as a result of upward flow.